Analisis Penggunaan Metode Gamifikasi untuk Meningkatkan Motivasi dan Hasil Belajar Siswa Pada Mata Pelajaran IPA-Biologi - Nofamataro Zebua; Padmaning Fathimah Pudya Malik; Nur Al-Azizah Al-Hilmiyah; Ester Novi Kurnia Zebua; Paulina Elvi Pebrianti; Murni Sapta Sari; Rudiyanto Rudiyanto (Jurnal Cakrawala Pendidikan dan Biologi, 2024)
Learning motivation is an important factor in the success of learning. However, low student motivation and learning outcomes are still a major problem in science-biology learning at Sriwedari Junior High School. This study aims to analyze the role of gamification as an innovative learning method that can improve students' motivation, engagement, and learning outcomes. The research used a descriptive qualitative approach involving students in grades VII, VIII, and IX as research subjects. Data was collected through in-depth interviews and documentation. The results showed that the use of gamification elements such as points, badges, and leaderboards managed to significantly increase students' motivation. In addition, students' active engagement in learning increased, seen from consistent attendance and participation in group discussions. Student learning outcomes also improved, with 75% of students achieving scores above the KKM after the implementation of gamification. Gamification creates interactive and relevant learning, allowing students to understand complex concepts more deeply. In conclusion, gamification is an effective approach to improve the quality of science-biology learning. Teachers are advised to strategically integrate gamification elements to create a fun and meaningful learning experience.